Alternative justice in environmental matters (Revista de Investigaciones Universidad del Quindío, 2021)
Alternative justice is an access to self-compositional justice where dialogue and communication represent decision-making for the individual and collective good. In situations of conflict of interest in environmental matters (ejidos, water, soil, among others), decision-making must be born from the consensus of those who directly impact the environmental damage (action or omission) in conjunction with the competent authorities of The matter. For this, the techniques and tools provided by alternative mechanisms strengthen conflict processes that can be managed and resolved in a participatory and inclusive way. It is to be recognized that the Mexican State within its legislative competence has progressively proclaimed and established laws regarding the integration of alternative justice in environmental conflicts.
Keywords: criminology; justice system; victim